2012
DOI: 10.1089/ther.2012.0004
|View full text |Cite
|
Sign up to set email alerts
|

Serum Potassium Changes During Therapeutic Hypothermia After Out-of-Hospital Cardiac Arrest—Should It Be Treated?

Abstract: Serum potassium decreases significantly during the induction of TH (p=0.005). Potassium levels were not found to be different in patients with and without VF/VT in this study, perhaps due to the low number of patients, as a difference has been seen in other studies. It is recommended that an infusion of supplementary potassium be initiated during the early cooling phase in order to avoid severe hypokalemia (serum potassium <3.0 mmol/L) and terminated in due time before normothermia is reached during rewarming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
3
7
0
1
Order By: Relevance
“…Regarding dependence of potassium plasma level on body temperature, our data are concordant to clinical trials by Miryozev et al [25], Soeholm and Kirkegaard [24]. Nevertheless, none of the animals in our experiment reached severe spontaneous hypokalemia (<3.0 mmol/L) which is supposed to be associated with a higher incidence of VT during cooling phase by the clinical trials.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding dependence of potassium plasma level on body temperature, our data are concordant to clinical trials by Miryozev et al [25], Soeholm and Kirkegaard [24]. Nevertheless, none of the animals in our experiment reached severe spontaneous hypokalemia (<3.0 mmol/L) which is supposed to be associated with a higher incidence of VT during cooling phase by the clinical trials.…”
Section: Discussionsupporting
confidence: 91%
“…The most likely mechanisms of hypokalemia are hypothermia induced both intracellular shift ing and renal loss of potassium [115]. However, serum potassium is anticipated to become elevated when temperature gets raised during rewarming stage [116]. It is safe and practical to keep serum potassium above 3.0 milliequivalents per liter during sustainment stage to avoid both related fatal arrhythmia during sustainment stage and overt hyperkalemia dur ing rewarming stage [114,116].…”
Section: Shivering and Common Physiologic Responsementioning
confidence: 99%
“…However, serum potassium is anticipated to become elevated when temperature gets raised during rewarming stage [116]. It is safe and practical to keep serum potassium above 3.0 milliequivalents per liter during sustainment stage to avoid both related fatal arrhythmia during sustainment stage and overt hyperkalemia dur ing rewarming stage [114,116]. Raised serum amylase is also common during sustainment stage; nonetheless, this elevated serum amylase is not related with clinical pancreatitis any more [117].…”
Section: Shivering and Common Physiologic Responsementioning
confidence: 99%
“…Rebound hyperkalemia on warming did not occur. Soeholm et al prospectively studied 54 patients and found that potassium levels dropped to below 3.5 mmol/l in 78% of TTM patients 141 . Both of these studies recommended that potassium levels be kept above 3.0 mmol/l during the hypothermic phase of TTM.…”
Section: Quality Of Evidence: Low Strength Of Recommendation: Conditimentioning
confidence: 99%